A Positioning Map and Future Research Agenda of Collaborative Consumption - Damayanti Octavia; Gatot Yudoko; Reza Ashari Nasution (Institut Teknologi Sepuluh Nopember, 2020)
Collaborative consumption (CC) is the new business model which overlaps with the concept of sharing economy (SE). However, CC has some unique characteristics that are not found in SE. This study aims to compare the two based on three dimensions: compensation, ownership, and platform. E- Commerce (EC) is included into the comparison in order to show that CC is actually a combination of SE and EC, thus covering a larger set than the other two concepts. The method used in this study is the literature study. The methods used CC concept manually and VOSviewer software to reassure and explore the unique characteristics of CC in comparison with SE and EC. The positioning map based on two dimensions: compensation and platform generate six business models that can be represented the characteristic of CC, SE, and EC. The six models are: (1) platform-based and monetary compensation; (2) platform-based and non-monetary compensation; (3) platform-based and without compensation; (4) non-platform-based and monetary compensation; (5) non-platform-based and non-monetary compensation; (6) non-platform-based and without compensation. The last dimension is ownership describe that CC activity is including exchange-based and access-based activity, while SE provides access-based activity only and EC offering exchange-based activity. The study also aims to discover the unique characteristics of CC that will be used as the basis for developing a future research agenda of CC.